489POverall survival in patients with EGFRm+ NSCLC receiving sequential afatinib and osimertinib: Updated analysis of the GioTag study. (24th November 2019) - Hochmair, M J; Morabito, A; Hao, D; Yang, C-T; Soo, R A; Yang, J C-H; Gucalp, R; Halmos, B; Wang, L; Märten, A; Cufer, T
Abstract: Background: Identifying the optimal sequence of EGFR TKIs is important to maximise survival in EGFR mutation-positive (EGFRm+) NSCLC. The observational GioTag study (NCT03370770) investigated outcomes in patients (pts) with EGFRm+ NSCLC who were treated with sequential afatinib and osimertinib in a 'real-world' clinical setting, including pts with poor prognosis (ECOG PS ≥ 2: 15%; stable brain metastases: 10%). 1 In the primary analysis, time to treatment failure (TTF) was 27.6 months in the overall population, 30.3 months in Del19-positive pts, and 46.7 months in Asians. Here we report overall survival (OS) and updated TTF. Methods: Data were retrospectively collected from Dec 2017–June 2018 for 203 pts with EGFRm + (Del19, L858R) NSCLC who were T790M positive after first-line afatinib and subsequently received osimertinib. TTF was the primary outcome; OS analysis was exploratory. Data were collected from electronic health records (EHRs; n = 126) or medical charts (n = 77). For logistical reasons, this interim analysis includes updated data (at April 2019) from pts with available EHRs (all USA; n = 94); final analysis with updated data from manual chart reviews is anticipated in early 2020. Results: After median follow-up of 30.3 months, median OS was 41.3 months (90% CI: 36.8–46.3) in the overall dataset (n = 203) and 45.7 months (90% CI: 45.3–51.5) in Del19-positive pts (n = 149); 2-year OS was 80%. OS in Asians was immature. Updated median TTF was 28.1 months (90% CI: 26.8–30.3) in all pts, and 30.6 months (90% CI: 27.6–32.0) in Del19-positive pts. Median TTF with osimertinib was 15.6 months (90% CI: 13.8–17.1) in the overall dataset, and 16.4 months (90% CI: 14.9–17.9) in Del19-positive pts. Median time from osimertinib discontinuation to death was 8 months. In 168 pts starting on afatinib 40 mg, median OS was 45.3 months (90% CI: 37.6–47.6); median TTF was 28.1 months (90% CI: 26.8–30.6). Conclusions: Encouraging OS and TTF was seen in pts with EGFR T790M-positive NSCLC with sequential afatinib and osimertinib, especially Del19-positive pts. Of note, prior afatinib treatment did not preclude prolonged TTF with second-line osimertinib. 1. Hochmair MJ, et al. Future Oncol. 2018;14:2861–74. Clinical trial identification: NCT03370770. Editorial acknowledgement: Lynn Pritchard of GeoMed, an Ashfield company, part of UDG Healthcare plc. Legal entity responsible for the study: Boehringer Ingelheim. Funding: Boehringer Ingelheim. Disclosure: M.J. Hochmair: Honoraria (self): AstraZeneca; Honoraria (self): Bristol-Myers Squibb; Honoraria (self), Advisory / Consultancy: Boehringer Ingelheim; Honoraria (self), Advisory / Consultancy: Merck Sharp & Dohme; Honoraria (self): Pfizer; Honoraria (self), Advisory / Consultancy: Roche; Advisory / Consultancy: Novartis. A. Morabito: Honoraria (self): Roche; Honoraria (self): AstraZeneca; Honoraria (self): Pfizer; Honoraria (self): Boehringer Ingelheim; Honoraria (self): Bristol-Myers Squibb; Honoraria (self): Merck Sharp and Dohme. D. Hao: Advisory / Consultancy, Research grant / Funding (self): Boehringer Ingelheim; Advisory / Consultancy, Research grant / Funding (self): AstraZeneca. R.A. Soo: Honoraria (self), Advisory / Consultancy, Research grant / Funding (self): AstraZeneca; Honoraria (self), Advisory / Consultancy: Bristol-Myers Squibb; Honoraria (self), Advisory / Consultancy, Research grant / Funding (self): Boehringer Ingelheim; Honoraria (self), Advisory / Consultancy: Celgene; Honoraria (self), Advisory / Consultancy: Ignyta; Honoraria (self), Advisory / Consultancy: Lilly; Honoraria (self), Advisory / Consultancy: Merck; Honoraria (self), Advisory / Consultancy: Novartis; Honoraria (self), Advisory / Consultancy: Pfizer; Honoraria (self), Advisory / Consultancy: Roche; Honoraria (self), Advisory / Consultancy: Taiho; Honoraria (self), Advisory / Consultancy: Takeda; Honoraria (self), Advisory / Consultancy: Yuhan. J.C-H. Yang: Honoraria (self): Merck Sharp and Dohme; Advisory / Consultancy: Merck Serono; Honoraria (self): Novartis; Advisory / Consultancy: Celgene; Advisory / Consultancy: Merrimack; Advisory / Consultancy: Yuhan Pharmaceuticals; Honoraria (self): Bristol-Myers Squibb; Honoraria (self): Ono pharmaceuticals; Advisory / Consultancy: Daiichi Sankyo; Advisory / Consultancy: Hansoh Pharmaceuticals; Advisory / Consultancy: Takeda Pharmaceuticals; Advisory / Consultancy: Blueprint Medicines; Advisory / Consultancy: G1 Therapeutics; Honoraria (self): Pfizer. B. Halmos: Advisory / Consultancy, Research grant / Funding (self): AstraZeneca; Advisory / Consultancy, Research grant / Funding (self): Pfizer; Honoraria (self), Advisory / Consultancy: Novartis; Advisory / Consultancy, Research grant / Funding (self): Merck Sharp and Dohme; Advisory / Consultancy, Research grant / Funding (self): Bristol-Myers Squibb; Advisory / Consultancy, Research grant / Funding (self): Boehringer Ingelheim; Advisory / Consultancy: Genentech; Advisory / Consultancy: Spectrum; Advisory / Consultancy: Ignyta; Research grant / Funding (self): Takeda; Research grant / Funding (self): Guardant Health; Research grant / Funding (self): Mirati; Research grant / Funding (self): AbbVie; Research grant / Funding (self): Novartis; Research grant / Funding (self): GSK; Advisory / Consultancy: Foundation Medicine; Advisory / Consultancy: Guardant Health. L. Wang: Full / Part-time employment: Boehringer Ingelheim. A. Märten: Full / Part-time employment: Boehringer Ingelheim. T. Cufer: Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: Roche; Honoraria (self), Advisory / Consultancy: Pfizer; Honoraria (self), Advisory / Consultancy: Merck Sharp and Dohme; Honoraria (self), Advisory / Consultancy: Bristol-Myers Squibb; Honoraria (self), Advisory / Consultancy: Boehringer Ingelheim. All other authors have declared no conflicts of interest.